The Effect of Thionamide to TRH, TSH, IL-4, T-REG, and Anti-TPO in Graves’ Disease - Eva Decroli; Dwitya Elvira; Dinda Aprilia (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2019)
The most common cause of hyperthyroidism is Graves' disease. TRH and TSH are hormonal factors that modulate and control thyroid function in Graves' disease. In the immunological aspect, Graves' disease is played by the role of T-reg, IL-4, and anti-TPO. Graves' disease treatment goal is to inhibit thyroid hormone secretion by administering thionamide. The evaluation of this treatment is its hormonal and immunological aspects. To describe the effect of thionamide on serum TRH, TSH, IL-4, T-reg, and anti-TPO levels in Graves' disease. This study is a clinical trial study in 25 study participants. All study participants were given thionamide, namely PTU 300mg for three months and blood samples were taken for laboratory tests. Serum TRH, TSH, IL-4, T-reg FOXP3, and anti-TPO levels were examined by ELISA. The mean levels at the beginning and after three months of therapy are: serum TRH 92.589pg/mL and 115.944pg/mL; serum TSH 0.041mU/L and 0.223mU/L; serum IL-4 19.759pg/mL and 23.040pg/mL; T-reg FOXP3 gene polymorphism 0.621ng/mL and 0.518 ng/mL; serum anti-TPO 2697.539pg/mL and 2604.710pg/mL. Increased levels of serum TRH and TSH levels were statistically significant. The change in serum IL-4, T-reg FOXP3 gene polymorphism, and anti-TPO levels were not statistically significant. The administration of thionamide in Graves' disease for three months will significantly decrease Wayne index and serum FT4 levels, increase serum TRH and TSH levels.